Diversitas Pangan Fermentasi Berbasis-Susu di Indonesia dan Kandungan Gizinya - Firyal Noviatanti Nabilah; Sri Listiyowati; Rika Indri Astuti (Institut Pertanian Bogor, 2022)
Indonesia has abundant and diverse food commodities, including fermented food. However, metadata analysis about the diversity of fermented foods has not been reported. In addition, a comparison of the nutritional content of milk-based fermented foods is also not yet available. Therefore, this study aims to reveal the diverse status of fermented foods, to determine the nutritional content, especially of fermented milk-based foods, namely dangke, and their comparisons between milk-based fermented products. The research method included literature study, making dangke, proximate analysis of dangke, and statistical data analysis. Literature studies show that fermented foods and beverages in Indonesia were most reported in 2017, 2018, and 2019 respectively. Although most fermented foods are not known for their area of origin, the microbial groups involved in their processing come from the bacterial group rather than fungi, mainly through the lactic acid fermentation mechanism. Microbes' role in fermented products is diverse and can be grouped into five groups. The primary role of microbes is to support bioprocesses. Among milk-based fermented products, dangke is one of the traditional products with a fat content that is significantly different fat content from yogurt, kefir, and dadih, and the protein is not significantly different from yogurt, kefir, dadih, and mozzarella cheese. This nutritional content analysis indicates differences in fat and protein content among fermented milk-based food products. Keywords: dangke, fat content, metadata, protein content, proximate analysis